The cost of personal investment: assessing the impact of student loan debt on financial outcomes before and during the federal payment and interest pause - Collier, Nathan (My University, 2025)
This study analyzed the impact of student loan borrowing on retirement savings, homeownership, and financial stress. Prior literature primarily focused on the dollar amount of student loan payments. This research considered the total amount of debt compared to income. The Human Capital Theory developed by Becker (1962) states that humans invest in their education to increase their earnings and overall economic outcomes. Human Capital framework tested the effectiveness of investment in education by focusing on the ratio of total student borrowing to the annual income received. During the COVID-19 pandemic, the interest and payments of federal student loans were paused. This research used data from the 2019 and 2022 waves of the Survey of Consumer Finances to compare the effects of student loan borrowing before and during the payment forbearance. This research adds to the body of knowledge regarding student loan debt by assessing the impact of the pandemic-induced forbearance, as well as providing further analysis of measuring student loan debt by total amount.
Keywords: Student loans; Homeownership; Financial stress; Debt-ratio; Payment pause